Effectiveness of Interpersonal Communication of Head of Farmer Group To Maintaining Existence Sidodadi Farmer Group - Prasetyo, Agus Subhan; Safitri, Reza; Hidayat, Kliwon (HABITAT, 2017)
The success of the farmer group depends on communication skills of the head of farmer group. Hence, the head of Sidodadi farmer group need a right communication to convey the information to group members. Appropriate communication will affect the members to receive a message delivered by the head of Sidodadi farmer group properly. Either communication do by the head of the Sidodadi farmer group is interpersonal communication. This research aims to describe the farmer’s group effectiveness of interpersonal communication to keep Sidodadi farmers’ group maintained. The analysis method that used in this research was descriptive analysis. The result of this research shows that interpersonal communication the head of Sidodadi farmer group has been effective. Effectiveness of interpersonal communication the head of Sidodadi farmer group can be seen from the attitude of the head of Sidodadi farmer group such as open attitude, empathy attitude, support attitude, positive attitude and equality attitude. With the effectiveness of interpersonal communication, the head of the farmer group made the existence of head of Sidodadi farmer group to be maintained.